2017
DOI: 10.1007/s10803-017-3220-3
|View full text |Cite
|
Sign up to set email alerts
|

Vicarious Effort-Based Decision-Making in Autism Spectrum Disorders

Abstract: This study investigated vicarious effort-based decision-making in 50 adolescents with autism spectrum disorders (ASD) compared to 32 controls using the Effort Expenditure for Rewards Task. Participants made choices to win money for themselves or for another person. When choosing for themselves, the ASD group exhibited relatively similar patterns of effort-based decision-making across reward parameters. However, when choosing for another person, the ASD group demonstrated relatively decreased sensitivity to rew… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
15
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 56 publications
(83 reference statements)
3
15
1
Order By: Relevance
“…VENs have been found to be absent or dysmorphic in various disease processes such as autism (Santos et al, 2011), schizophrenia (Brüne et al, 2011), and agenesis of the corpus callosum (Kaufman et al, 2008). These three disorders are related to alterations in effort-based decision-making (Brown et al, 2012;Damiano et al, 2012;Fervaha et al, 2013;Gold et al, 2013;Treadway et al, 2015;Mosner et al, 2017;Culbreth et al, 2018).…”
Section: Intrinsic Organization and Specificity Of The Cortical Colummentioning
confidence: 99%
“…VENs have been found to be absent or dysmorphic in various disease processes such as autism (Santos et al, 2011), schizophrenia (Brüne et al, 2011), and agenesis of the corpus callosum (Kaufman et al, 2008). These three disorders are related to alterations in effort-based decision-making (Brown et al, 2012;Damiano et al, 2012;Fervaha et al, 2013;Gold et al, 2013;Treadway et al, 2015;Mosner et al, 2017;Culbreth et al, 2018).…”
Section: Intrinsic Organization and Specificity Of The Cortical Colummentioning
confidence: 99%
“…Additionally, although delay and social discounting tasks both involve reward processing, only social discounting involves the reward of giving to another, which may recruit social‐cognitive brain networks outside of the reward system (Morelli, Sacchet, & Zaki, ). There is some limited evidence for atypical processing of others' rewards in autism (Mosner et al, ), but the construct remains understudied in ASD despite its core role in human social relationships (Morelli, Lieberman, & Zaki, ).…”
Section: Introductionmentioning
confidence: 99%
“…e MTG has also previously been implicated in theory of mind abilities [62,63], social perception [64], and empathic judgements [65], and relatively diminished activation within the MTG in individuals with ASD has previously been reported in response to social mentalizing tasks [66,67]. Taken together, ASD hypoactivation in the MTG may underlie observed deficits in behavioral vicarious reward responses [25], as well as broader social cognitive deficits inherent to the disorder. Whereas the TDC vicarious reward literature does not specifically implicate striatal regions as being preferentially activated for vicarious reward processing [16], it is noteworthy that individuals with ASD showed reduced activation during vicarious reward outcomes in the caudate nucleus, given its established role in reward processing.…”
Section: Discussionmentioning
confidence: 97%
“…Individuals with ASD appear to be somewhat immune to this effect and are equally generous whether they are observed or not [18]. Furthermore, Mosner et al [25] reported that individuals with ASD demonstrated unimpaired expended effort for monetary rewards for oneself, but they demonstrated reduced sensitivity to reward magnitude parameters when earning rewards for others. Taken together, these behavioral findings support a hypothesis of altered vicarious reward processing in ASD.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation